Penentuan Stabilitas Penyimpanan Aspal Modifikasi Berbasis Karet Alam Padat Jenis Crumb Rubber - Arya Wiranata (Journal of Bioprocess, Chemical and Environmental Engineering Science, 2021)
The development of road infrastructure in Indonesia is very rapid to keep pace with the growth of vehicles. However, the structure of road pavements in Indonesia is not optimal and causes various problems due to overload and Indonesia's climate. Therefore, it is necessary to increase the performance of asphalt binders with additives such as natural rubber or better known as natural rubber modified asphalt. This study examines the effect of natural rubber content (crumb rubber standard Indonesian rubber 20), sulfur additive content, storage temperature, and storage time on the phase stability of natural rubber modified asphalt. Making crumb rubber modified asphalt samples begins with the mastication of crumb rubber in an open mill. Next, crumb rubber was melted at 200°C and mixed in asphalt with 8, 10, and 12% levels. The last stage is to test the stability of modified asphalt storage at a temperature of 160°C for 48 hours. The results showed that modified asphalt with various levels of rubber experienced storage stability problems after 48 hours. The addition of sulfur additives did not significantly affect storage stability. The optimum addition of natural rubber at 10% crumb rubber content with the difference in softening point (Tbottom – Ttop) reached 11.6°C.